Developing of an automation for therapy dosimetry systems by using labview software - Aydin, Selim; Kam, Erol (ELSEVIER SCIENCE BV, 2018)
Traceability, accuracy and consistency of radiation measurements are essential in radiation dosimetry, particularly in radiotherapy, where the outcome of treatments is highly dependent on the radiation dose delivered to patients. Therefore it is very important to provide reliable, accurate and fast calibration services for therapy dosimeters since the radiation dose delivered to a radiotherapy patient is directly related to accuracy and reliability of these devices. In this study, we report the performance of in-house developed computer controlled data acquisition and monitoring software for the commercially available radiation therapy electrometers. LabVIEW (R) software suite is used to provide reliable, fast and accurate calibration services. The software also collects environmental data such as temperature, pressure and humidity in order to use to use these them in correction factor calculations. By using this software tool, a better control over the calibration process is achieved and the need for human intervention is reduced. This is the first software that can control frequently used dosimeter systems, in radiation thereapy field at hospitals, such as Unidos Webline, Unidos E, Dose-1 and PC Electrometers. (C) 2018 Published by Elsevier B.V.
Keywords: Radiation dosimeter calibration; Therapy level dosimetry systems; DAQ and Monitoring; Materials Science; Physics